Assembly of breast cancer heterotypic spheroids on hyaluronic acid coated surfaces - Carvalho, Marco António Paulo de (2018)
Drug screening is currently demanding for realistic models that are able to reproduce the structural features of solid tumors. 3D cell culture systems, namely spheroids, emerged as a promising approach to provide reliable results during drug development. So far, liquid overlay technique (LOT) is one of the most used methods for spheroids assembly. It comprises cellular aggregation due to their limited adhesion to certain biomaterials, like agarose. However, researchers are currently improving this technique in order to obtain spheroids on surfaces that mimic cancer extracellular matrix (ECM), since cell–ECM interactions modulate cells behavior and their drug resistance profile. Herein, hyaluronic acid (HA) coated surfaces were used, for the first time, for the production of reproducible heterotypic breast cancer spheroids. The obtained results revealed that it is possible to control the size, shape, and number of spheroids gotten per well by changing the HA concentration and the number of cells initially seeded in each well.